Usability of the medical mobile application for patients: Kazakhstani case - Orazgaliyeva, E.B.; Smykova, M.R.; Abuzhalitova, A.A. (BUKETOV BUSINESS REVIEW, 2023)
Object: Covid-19 pandemic was impact in all aspects of our life, especially digital health care. This study was aimed to examine the usability of the state medical mobile application called Damumed with neuromarketing tool – eye-tracking. Damumed is the main state health information system designed to facilitate the work of medical personnel, thereby improving the quality and accessibility of medical services for patients, where patients can find all medical appointments, health passport and all health-related information. This research is aimed to achieve SIG Goal of Good health and well-being for people. Methods. Using neuromarketing instrument with unstructured interviews to identify key features of usability aspects of the medical mobile application. Findings: Overall, 23 patients were separated into 2 age groups of young (18-24) and adults (35-44). They engaged in the study to participate both in neuromarketing research and unstructured interviews. Adults had difficulties in understanding the navigation of the app, while younger group could navigate in the app intuitively. Conclusions. Neuromarketing studies and individual interviews clarified assessing the usability of the medical mobile application interface. Since the respondents have different background, for adults it was a bit challenging to assess the app’s interface. In this respect, for older generation would a barrier to adopt this kind of information systems.